Kajian Kriminologis Tindak Pidana Pencurian Ikan Segar dalam Kapal Motor Nelayan Dermaga Dirgahayu Kecamatan Rantau Rasau Kabupaten Tanjung Jabung Timur - Muhammad Chairul Idrah; Iman Hidayat (Wajah Hukum, 2022)
Theft is one of the categories of crimes against human property/wealth and is classified as one of the crimes regulated in the criminal code of law. Theft is an act of crime that has been rampant in society, so that the safety and comfort of people’s lives is greatly disturbed. The factors that cause theft are found within the perpetrator, which means that what influrnces a person to commit a crime arises from within the perpetrator himself, which is based on heredity and psychology.